Conventional Radiological Findings of an Anterior Mediastinal Mass at Ngoerah Hospital - Putu Patriawan; Lorensius Ivan Pantekosta; Dewa Gde Mahiswara Suadiatmika (KOLONI, 2026)
The most common anterior masses, often referred to by the acronym 4T, consist of thymoma, teratoma, thyroid tissue, and lymphoma (terrible lymphoma). These masses present unique challenges due to their proximity to critical thoracic structures. Although advances in imaging aid in characterization, an accurate diagnosis often requires a multimodal approach integrating radiological, histological, and molecular techniques. The anterior mediastinum, located in front of the heart and bounded by the sternum, undergoes significant changes from childhood to adulthood. In children, the mediastinum houses the large thymus, a vital immune organ; in adults, the mediastinum transitions into a smaller space as thymic function diminishes and the gland atrophies. This evolution leaves an area vulnerable to tumor formation. This case report discusses three distinct cases of anterior mediastinal masses. From the cases presented, it is evident that chest radiography plays a crucial role in establishing the initial diagnosis of patients with mediastinal abnormalities, specifically anterior mediastinal masses. However, in the previously discussed cases, only a single-projection chest X-ray—the posterolateral (PA) view—was performed. As explained in the available literature, in patients suspected of having mediastinal abnormalities, chest X-rays should be performed using two projections: posteroanterior and lateral.